2009
DOI: 10.1002/cncr.24304
|View full text |Cite
|
Sign up to set email alerts
|

The calcium‐sensing receptor and parathyroid hormone‐related protein are expressed in differentiated, favorable neuroblastic tumors

Abstract: Objective Lubricin, also referred to as superficial zone protein and PRG4, is a synovial glycoprotein that supplies a friction‐resistant, antiadhesive coating to the surfaces of articular cartilage, thereby protecting against arthritis‐associated tissue wear and degradation. This study was undertaken to generate and characterize a novel recombinant lubricin protein construct, LUB:1, and to evaluate its therapeutic efficacy following intraarticular delivery in a rat model of osteoarthritis (OA). Methods Binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Our observations of a synergic up-regulation of CaSR and the neurogenic biomarker Nestin mRNA levels, by both CaSR agonists (Ca 2+ and AMG641) and in both cell lines, even associated with non quantitatively relevant effects on Nissl bodies formation and beta III tubulin immunopositivity, support our hypothesis that CaSR is involved in early-stage neurogenic differentiation of UCM-MSCs, as reported in previous studies in other cell systems [72]. The stimulatory effects of the CaSR agonist observed in our study are also in line with those reported by Vizard et al, [45] who showed that activating CaSR in perinatal sympathetic neurons with the calcimimetic NPS R-467 enhances axonal and dendritic growth in culture and this effect is reversed by the selective CaSR antagonist NPS89636 and cannot be obtained in CaSR deficient mice.…”
Section: Discussionsupporting
confidence: 91%
“…Our observations of a synergic up-regulation of CaSR and the neurogenic biomarker Nestin mRNA levels, by both CaSR agonists (Ca 2+ and AMG641) and in both cell lines, even associated with non quantitatively relevant effects on Nissl bodies formation and beta III tubulin immunopositivity, support our hypothesis that CaSR is involved in early-stage neurogenic differentiation of UCM-MSCs, as reported in previous studies in other cell systems [72]. The stimulatory effects of the CaSR agonist observed in our study are also in line with those reported by Vizard et al, [45] who showed that activating CaSR in perinatal sympathetic neurons with the calcimimetic NPS R-467 enhances axonal and dendritic growth in culture and this effect is reversed by the selective CaSR antagonist NPS89636 and cannot be obtained in CaSR deficient mice.…”
Section: Discussionsupporting
confidence: 91%
“…This GPCR is also expressed in many organs not involved in calcium homeostasis and in some neoplasias in which it plays cell-type specific functions [13]. Our initial work showed that CaSR is expressed in benign, differentiated neuroblastic tumors and upregulated upon differentiation induction [14]. Next, we reported that the CaSR gene is silenced by genetic and epigenetic mechanisms in MYCN-amplified, unfavorable neuroblastomas [15].…”
Section: Introductionmentioning
confidence: 96%
“…Sections (4 μm) of formalin fixed, paraffinembedded tumors were stained with haematoxylin eosin (H&E), Masson's trichrome or processed for immunohistochemistry to analyze CaSR expression as described [14]. A similar protocol was carried out with antiGAGE7 (Life Technologies) and antihuman nuclei, clone 3E1.3 (MerckMillipore, Darmstadt, Germany).…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, PTHrP has been shown to regulate cell growth, differentiation and survival [14]. Up-regulation of PTHrP in cancer cells has been demonstrated in breast, prostate and lung cancer, neuroblastic tumors, ATLL and other cancers [15]. PTHrP functions mainly by binding to its membrane receptor, PTH1R.…”
Section: Introductionmentioning
confidence: 99%